Association of health literacy with cancer survival: a single-centre prospective cohort study - Sandström, Niclas; Jekunen, Antti; Johansson, Mikael; Andersén, Heidi (MJS Publishing, Medical Journals Sweden AB, 2025)
Background and purpose: Health literacy is defined as the ability to find, understand and use health information for informed decision. The role of health literacy in treatment decisions and outcome remains largely unexplored. This study sought out to assess the effect of individual health literacy on overall survival (OS) in cancer patients in Ostrobothnia.
Material and methods: The present study is a follow-up of a cross-sectional survey study performed during December 2021 and March 2022. The survey assessed socioeconomic factors, lifestyle factors and self-reported health literacy. The follow-up included data on recorded death, cause of death, performance status (PS), clinical frailty scale, Charlson comorbidity index and body mass index. The sample size for this study was 400 participants, and any participant with a malignancy was eligible for the study.
Results: Low health literacy was associated with increased risk of death. The disparity remained after adjustments for age, sex, comorbidities, PS, stage and hazard ratios (HR) = 1.47 (1.01–2.14). After adjustments for lifestyle patterns, the disparity remained, HR = 1.49 (1.03–2.17). The difference diminished after adjustments for cancer types. The median OS was 3.6 months longer for those with medium-high health literacy than those with low health literacy.
Interpretation: The results indicated health literacy having a direct, clinically significant, effect on OS, which is likely not explained by differences in cancer entity alone. Future studies should focus on assessing whether an intervention aiming to improve health literacy may improve overall cancer survival.